A Guided Search for Races Based on Data Flow Patterns - Neubaum, Andreas; Al Sardy, Loui; Spisländer, Marc; Saglietti, Francesca; Kretschmer, Sara (Lecture Notes in Computer Science (LNCS), 2022)
A strategy for searching for exploitable races is derived, implemented and evaluated. It aims at the detection of inconsistent behaviour due to irregularly interleaved instructions of concurrent threads. The search for internal races focuses on particular data flow patterns targeting the occurrence of internal races by enforcing different orders of reading and writing operations; it is guided by symbolic expressions of interleaved paths and constraint solving. The possibility of propagating internal races to system races is subsequently considered. An exemplifying application of the approach proposed illustrates its practicality.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Constraint solving; Data flow pattern; Interleaving; Race; Scheduling; Software vulnerability; Symbolic execution; Thread